Uji Potensi Biogas Eceng Gondok (Eichhornia crassipes) dengan Jeroan Ikan Patin (Pangasius sp.) dan Kotoran Kuda - Multi Idola Tricia; Indah Widiastuti; Susi Lestari (Jurnal FishtecH, 2017)
This research used randomized block design with 2 repetitions as the group and five treatments. The treatments were the percentage of horse manure (KK) and waste catfish (LP): A1 KK (100%), A2 KK (75%) + LP (25%), A3 KK (50%) + LP (50%), A4 KK (25%) + LP (25%) and A5 LP (100%). The parameters observed were volume of biogas, biogas production rate and parameters on slurry includes pH, temperature, total solid, chemical oxygen demand and the ratio C/N. The results showed that the high volume of biogas produced by A1 was equal to 4,206.5 mL with a pH of 7.62 and 4.29% and a total solid ratio C/N 30.02. Biogas produced ranged between 520 to 4,206.5 mL. The acidity ranged from 7.62 to 6.23. The resulting temperature ranged from 29.56 to 30.79 Â°C. Total solid produced ranged between 4.29 to 5.66%. Chemical oxygen demand generated ranged from 55,880.5 to 117,361.1 mg/kg. Ratio C/N produced ranged from 7.29 to 30.02. The addition viscera of catfish effected on changed in pH, total solid, ratio C/N and the amount of biogas produced.